Peran Pemerintah Dalam Membenahi Kualitas Pelayanan Publik di Bidang Kesehatan - Chairun Nisa Dwi Putri; Fath Diene Yuslima Handaruan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The problems in the health sector that are being faced by the Indonesian government are the unequal distribution of health facilities and the lack of health facilities available to the community. This results in the community not getting optimal services in obtaining public services, especially in health care facilities. The problems caused by the lack of these facilities have a very fatal impact on the community, especially in the health sector which is directly related to human life. This is an important task for the government to improve services in the health sector, especially health facilities in order to provide the best public services for the community because maintaining and protecting the right to life (life) of the community is the duty and obligation of the community. government. This has been regulated in Article 27 Paragraph (2) of the 1945 Constitution of the Republic of Indonesia. The purpose of this paper is that the government is more concerned in handling public health center facilities in order to fulfill the satisfaction rate of the community towards public services, especially public health center. Data collection techniques were carried out qualitatively and descriptively by dissecting books, articles and journals.